MODULAR APPROACH TO THE MUSIC-PEDAGOGIC TRAINING - Anna P. Mansurova (Высшее образование в России)
This article considers the main tendencies in the sphere of higher education in the music teaching profession in the context of problems of European integration, the ways of realization of modular approach to the music-pedagogic training at the university. The article touches on the issues of modular structure of education by the example of training of a musicteacher for a general school. The features of a learning module as a means of forming of music-pedagogical competences are viewed.